PENGENALAN PROGRAM ARTIFICIAL INTELLIGENCE PADA PENGURUS MASJID ISLAMIC VILLAGE TANGERANG - Firdaus, Mohamad; Indra Bakti (CV. Denasya Smart Publisher, 2025)
The advancement of digital technology today has brought forth various applications based on Artificial Intelligence (AI) that can be utilized to support organizational management activities, including mosque management. This community service activity aims to introduce the basic concepts of AI and its potential applications in supporting the activities of mosque administrators in the Islamic Village Tangerang area. The activity was conducted online through socialization sessions and interactive discussions, covering materials on AI introduction, examples of simple AI implementations, and discussions on opportunities for its application in mosque administration and digital da'wah media. This activity was successfully carried out, and the results showed an increase in participants' understanding of basic AI concepts as well as enthusiasm to further develop the use of this technology within the mosque environment. This program is expected to serve as a starting point for mosque administrators in utilizing AI technology in a positive and productive manner.